J. Donald Gillaspey letter to Woodward H. Brown regarding birds seen in Lamoni, Iowa, during winter 1971-1972, February 14, 1972 - Gillaspey, J. Donaldet al (1972)
Letter from J. Donald Gillaspey to Woodward H. Brown regarding birds seen in Lamoni, Iowa, during the winter of 1971-1972. Gillaspey reports an unusual winter sighting of Brewer's Blackbirds at Lamoni and notes that no Short-eared Owls were seen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1971-1972. Epson - sheet feed/flatbed